Social Media Effect: Building the Customers Loyalty of Hennes & Mauritz Brand Fashion in Indonesia - Liesta Augustine; Rewindinar Rewindinar; Rustono Farady Marta (Universitas Pendidikan Ganesha, 2021)
Economic growth has accelerated in recent years. Company owners’ tactic was to used social media as a bridge to reach out to customers. A brand gains who gains consumers would attempt to establish a relationship with them and also gain their commitment. This is referred to as consumer loyalty. This loyalty was very critical to the brand’s long term sustainability and growth. Customers’ satisfaction can be used to gain customer loyalty. This study aims to examine H&M's use of Twitter as a social networking platform for building consumer loyalty. This study used a netnographic approach to examine H&M's marketing strategy for building consumer loyalty through the use of social media, specifically Twitter. The netnography approach is an ethnographic method that combines the use of internet with ethnography. The data for this analysis was gathered by reprocessing H&M post data obtained via Twitter. The findings in this research conclude that games and interaction will undoubtedly be required to capture customers' interest and generate their loyalty. Essentially, consumers' willingness to be in touch with a company decides whether or not they want to give commitment. This commitment will determine the customers’ loyalty by their behaviour in purchase continuously. As a result, it's possible to reduce those customers has chosen to make H&M brand their first preference which show a sign of customers’ loyalty.